Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1563/aaid-joi-d-13-00108
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Retraction During Inferior Alveolar Nerve Repositioning Procedure: A New Simple Method and Review of the Literature

Abstract: Nerve repositioning surgery is one of the treatments chosen for the patients with edentulous posterior atrophic mandible. Like any other treatments, this therapy has its advantages and disadvantages, indications and contraindications. The most important complication of this procedure is neurosensory disturbance. This problem may occur at different stages of the treatment. One common time when nerve damage happens is when the nerve is located outside the canal and drilling and insertion of the implant are perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…There was no difference in MCBs between dentulous and edentulous samples. Previous reports showed the existence of small MCBs containing terminal nerves and blood vessels (Wadu et al 1997; Polland et al 2001; Hu et al 2007; Von Arx et al 2011; Yamada et al 2011; Kawai et al 2012; Hassani et al 2015; Aljunid et al 2016; Yu et al 2016; Afsa and Rahmati 2017). To understand the dynamics of the MCB in the alveolar bone, the present study comprehensively evaluated each element related to the MCB using PCA and defined the location of the MCB and the morphology of the bone around the MCB.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There was no difference in MCBs between dentulous and edentulous samples. Previous reports showed the existence of small MCBs containing terminal nerves and blood vessels (Wadu et al 1997; Polland et al 2001; Hu et al 2007; Von Arx et al 2011; Yamada et al 2011; Kawai et al 2012; Hassani et al 2015; Aljunid et al 2016; Yu et al 2016; Afsa and Rahmati 2017). To understand the dynamics of the MCB in the alveolar bone, the present study comprehensively evaluated each element related to the MCB using PCA and defined the location of the MCB and the morphology of the bone around the MCB.…”
Section: Discussionmentioning
confidence: 98%
“…Alveolar bone structures affect the periphery of the nerves and blood vessel supply (Polland et al 2001; Yu et al 2016). The existence of a branching mandibular canal was reported (Wadu et al 1997; Hu et al 2007; Yamada et al 2011 Hassani et al 2015; Aljunid et al 2016; Afsa and Rahmati 2017) using a simple analysis and cone-beam computed tomography (CBCT). The sympathetic and parasympathetic nerves control blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the use of corrugated rubber drain, we used to apply surgical glove, gauze, nasogastric tube (6 Fr or 8 Fr) to protect and retract the nerves away from the surgical field. In literature, use of low-thickness elastic or latex tapes is also [5] mentioned. As per our experience, we found that these techniques are less effective for protection of nerves as many problems are faced due to less thickness and small diameter of these materials leading to easy breakage leaving residues at surgical sites and also these materials are not capable of providing good hold of nerves and lead to an acute angulation of nerves during retraction which can cause neurological complications such as traction injury or neuropraxia.…”
Section: Prevention Of Nerve Injuriesmentioning
confidence: 99%
“…Commonly employed materials include use of glove sleeves, nasogastric tube, gauze pieces , low-thickness elastic tape or [5] low-thickness Latex tape .With the use of these techniques, few cases of intra-operative nerve injuries are still seen.…”
Section: Introductionmentioning
confidence: 99%
“…It easily herniates into the defect with a little teasing and is gently pulled out from its bed with a vascular clamp [8]. Since the main cause of sensory disturbances is the impairment of the metabolic supply due to the disturbed microvascular circulation of the nerve fibers by the mechanical trauma [34][35][36], surgeons should avoid the excessively and unnecessarily manipulating of the surgery site for finding the BFP. At this time, the external pressure helps the removal of the temporal extension of the BFP.…”
Section: Surgical Approachmentioning
confidence: 99%